Confusion and Compensation in Visual Perception: Effects of Spatiotemporal Proximity and Selective Attention - Christoph Weidemann (Journal of Experimental Psychology: Human Perception and Performance, 2005)
The authors investigated spatial, temporal, and attentional manipulations in a short-term repetition priming paradigm. Brief primes produced a strong preference to choose the primed alternative, whereas long primes had the opposite effect. However, a 2nd brief presentation of a long prime produced a preference for the primed word despite the long total prime duration. These surprising results are explained by a computational model that posits the offsetting components of source confusion (prime features are confused with target features) and discounting (evidence from primed features is discounted). The authors obtained compelling evidence for these components by showing how they can cooperate or compete through different manipulations of prime salience. The model allows for dissociations between prime salience and the magnitude of priming, thereby providing a unified account of "subliminal" and "supraliminal" priming.